2016
DOI: 10.1016/j.oraloncology.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy for squamous cell carcinomas of the oral cavity: A cumulative meta-analysis

Abstract: 27 randomized trials were included for analysis (n=2872 patients). The shortest median follow-up was 15months whereas the longest was 11.5years. ICT does not improve OS (HR=0.947, 95% CI 0.85-1.05, p=0.318), DFS (RR=1.05, 95% CI 0.92-1.21, p=0.462) and DM (RR=0.626, CI 95% 0.361-1.086, p=0.096) compared to locoregional treatment alone. However, there was a significant improvement to LRR (RR=0.778, 95% CI 0.622-0.972, p=0.027). There is no evidence ICT improves survival outcomes for OSCC patients. However, ICT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…CT can prove effective in advanced stage OSCC, but there is not evidence to support its benefits as an induction treatment [1,4,10,16]. Moreover, drug-related adverse side effects and acquired MDR limit its efficacy.…”
Section: Nano-based Chemotherapymentioning
confidence: 99%
“…CT can prove effective in advanced stage OSCC, but there is not evidence to support its benefits as an induction treatment [1,4,10,16]. Moreover, drug-related adverse side effects and acquired MDR limit its efficacy.…”
Section: Nano-based Chemotherapymentioning
confidence: 99%
“…Conflicting results have been reported by various randomised controlled clinical trials designed with different inclusion criteria to test different chemotherapeutic regimens; results from meta-analyses were also inconsistent ( Table 2). [3][4][5]9,10 The definitions of locally advanced cancer and therefore the population of patients included in these studies were heterogeneous, ranging from cT2N0 (>3 cm) to cT4N3. 3,4 TPF has been shown to be superior to PF in multiple clinical trials and this was also confirmed in a meta-analysis using individual patient data.…”
Section: Discussionmentioning
confidence: 99%
“…It is debatable whether our patient should be judged as resectable or non-resectable. Induction chemotherapy was reported to be ineffective for resectable OSCC ( 14 , 15 ). Standard therapy for non-resectable OSCC is CRT with high-dose CDDP ( 13 ), while induction chemotherapy with TPF therapy is also regarded as standard therapy in Europe ( 16 ).…”
Section: Discussionmentioning
confidence: 99%